Estimating the Neutral Interest Rate in the Kyrgyz Republic - Ruxandra Teodoru, Iulia (IMF Working Papers; Working Paper ;, 2020)
This paper estimates the neutral interest rate in the Kyrgyz Republic using a range of methodologies. Results indicate that the real neutral rate is about 4 percent based on an average of models and 3.7 percent based on a Quarterly Projection Model. This is higher than in many emerging markets and is likely explained by higher public debt and an elevated risk premium, low creditor rights and contractual enforcement, and low domestic savings. The use of an estimate of the neutral interest rate provides useful guidance to monetary policy and enhances transparency and independence of the central bank. Our estimate provides a quantitative benchmark for the monetary policy stance in the context of a central bank that is building analytical capacity, integrating additional insights in its decision-making process, and working to improve its communication. Strengthening the monetary transmission mechanism will be critical to enhance the effectiveness of monetary policy, including by allowing more exchange rate flexibility to support the transition to a full-fledged inflation targeting regime, and reducing excess liquidity to enhance the credit channel, reducing dollarization and high interest rate spreads that adversely affect the transmission of the policy rate to the economy.